2016
DOI: 10.1590/0074-02760160027
|View full text |Cite
|
Sign up to set email alerts
|

On triatomines, cockroaches and haemolymphagy under laboratory conditions: new discoveries

Abstract: For a long time, haematophagy was considered an obligate condition for triatomines (Hemiptera: Reduviidae) to complete their life cycle. Today, the ability to use haemolymphagy is suggested to represent an important survival strategy for some species, especially those in genus Belminus. As Eratyrus mucronatus and Triatoma boliviana are found with cockroaches in the Blaberinae subfamily in Bolivia, their developmental cycle from egg to adult under a “cockroach diet” was studied. The results suggested that havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Moreover, additional to hematophagy, members Triatominae have been documented to exhibit predacious behavior, [1722] which contributes to increasing the doubts about the subfamily monophyly, defined mainly by feeding habits. Indeed, if the hematophagous feeding habit independently appeared multiple times in the subfamily, Triatominae should be considered polyphyletic (Figure 2).…”
Section: Triatominae Monophyly Vs Paraphylymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, additional to hematophagy, members Triatominae have been documented to exhibit predacious behavior, [1722] which contributes to increasing the doubts about the subfamily monophyly, defined mainly by feeding habits. Indeed, if the hematophagous feeding habit independently appeared multiple times in the subfamily, Triatominae should be considered polyphyletic (Figure 2).…”
Section: Triatominae Monophyly Vs Paraphylymentioning
confidence: 99%
“…Built based on morphology, before DNA sequence data were readily available, both tribes have been shown to be monophyletic [1, 2224], however new DNA based phylogenetic data show that genera within each group are not (Figure 3, Key Figure). …”
Section: Triatominae Systematics: Taxonomy Vs Phylogenymentioning
confidence: 99%
“…This disparity may stem from inconsistencies between individual sample sets and methodology, but could also reflect Triatominae true biological characteristics. These include lengthy development times through five nymphal instars [38,42], complex physiology of the alimentary tract [38], and accessory feeding strategies, like hemolymphagy (feeding on arthropod haemolymph), kleptohematophagy (stealing a blood meal from another triatomine), and coprophagy (feeding on faeces) known to be employed by some triatomine species [2,[45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…These bugs are nest-living insects, and given that they share very intimately their nest with their host, are considered a type of ectoparasite (e.g., ticks and lice). Although most triatomines require vertebrate blood to survive, Sandoval et al (2015) have demonstrated by morphometric analysis that Belminus species are entomophagous; contrary to other triatomine species that have been observed practicing hemolymphagy on cockroaches but have not been demonstrated to be able to use such tactics as a prolonged survival strategy (Durán et al 2016). Furthermore, Díaz-Albiter et al (2016) found that Rhodnius prolixus is able to derive physiological benefit from water and sugars from tomatoes (Solanum lycopersicum).…”
Section: Introductionmentioning
confidence: 99%